DISEÑO MUSEOGRÁFICO DE LA SALA DE LA CULTURA PURUHÁ Y SU DINAMIZACIÓN PEDAGÓGICA, EN EL MUSEO DE LA CIUDAD DE RIOBAMBA. - Torres Cevallos, Jimena Alexandra (2019)
The purpose of this research is to make a museographic proposal design of Puruhá culture hall and its pedagogical dynamism, in Riobamba city museum to carry outeducational, creative and motivating activities, where the student, assimilate, feel and see in a better way all the knowledge they can learn all the message from content and they stored in their memory to be associated with they studied in the classroom. For this reason we have used a methodology that is consistent with this research project, existing a non-experimental qualitative study, to be an educational and social nature project in which different types of research will be used: field, basic and bibliographic type which helped in the construction of the proposal, focusing on the educational workshops of a museographic proposal design of Puruhá culture hall and its pedagogical dynamism in Riobamba city museum. The research project has as a results to improve the museographic design of this room, proposing a recreation of the history of the oldest civilization in the province of Chimborazo, with the support of the museographic method which allowed to adequate chronologically each of the archaeological pieces and vestiges to be exhibited in the room, facilitating the pedagogy dynamism to each visitors through the workshops, concluding with a pleasant and novel visit for the citizenship.